Colombia: Democracy, violence, and the peacebuilding challenge (2018)
After years of painstaking negotiations and political obstacles, the end to the conflict between the Revolutionary Armed Forces of Colombia (FARC) and the Colombian government appears irreversible. Daunting challenges to the implementation of the agreement remain, however. The five pieces in this special issue rigorously examine those challenges. In doing so, they explore how the field of peace science can help us understand Colombia’s transition from war to peace and how Colombia raises new unexplored questions for scholars. This introduction describes the principal findings of the special issue before offering tangible advice to peacebuilders working in Colombia. © The Author(s) 2018.